Male and female adolescents' perception of haptic communication in heterosexual friendships - Fernandez, Maria Lourdes Jay Yogore
This descriptive study sought to identify the most common types, contexts and interpretations of tough among heterosexual adolescent friendship based on response rate through a cluster and purposive sampling. A total of 46 respondents, 23 males and 23 females, aged 16-20 years old, participated in the study by answering the the two sets of survey questionnaires. Both surveys contained the same set of questions such as the types of touch they have received from friends of the opposite sex, context when they have received from friends of the opposite sex, context when they received it and their interpretations. Respondents who are students students from the University of the Philippines were asked to refer to their close friends of the opposite sex for the first survey and non-close for the second survey. Males and females reported similar types of tough they commonly receive from close and non-close friends. Looking into the contexts and interpretations, touches among non-close friends are less emotional and mostly revolve around the social/polite and professional/casual touch. Females were observed to be more sensitive to touch but are more touch-avoidant than males. While the study aims to look deeply into haptic communication in heterosexual frienship among Filipinos, it provides insight on social roles being played by adolescents and their maturation into adulthood. Future studies can focus on these areas of adolescence and also the type of child-rearing practices they have.